Effect of the Controllers With Control Delay on Vehicle-Guideway Coupling Vibration for Maglev Train at Standing Still - Keren Wang; Weihua Ma; Xiaohao Chen; Ruiming Zou (IEEE Access)
The commercial operation of maglev trains is significantly affected by vibrations resulting from the coupling between the vehicle and track. Previous research has primarily focused on single electromagnet suspension systems, neglecting the dynamic disparities between these systems and vehicle suspension systems. Furthermore, there is a lack of comprehensive analysis regarding instability mechanisms in the suspension of maglev trains on flexible track beams. To address these gaps, a vertical dynamics model for vehicle-guideway coupling was developed with three levitation frames. Initially, this study examined the impact of controller delays on the divergence rate between the vehicle and track beam when employing a double-loop PID control algorithm. Additionally, it analyzed how implementing a redundant control mode at levitation points influences vibration responses caused by these delays. The findings indicate that control delays have a more pronounced impact on the track beam compared to the vehicle system, making it more susceptible to initial vibration divergence. For instance, instability in the suspension system occurs when the time delay of the single-point suspension controller reaches about 2.146 ms. Moreover, utilizing a redundant control method for levitation points can partially alleviate coupling vibrations resulting from controller delays. For example, the instability of the suspension system can be caused by a controller delay exceeding about 7ms. Importantly, when the first-order vibration frequency of the track beam falls within a specific range and reaches a critical threshold for controller delay, energy supplied to the track beam by the levitation system can surpass its damping dissipation capacity, leading to sustained coupling vibrations.